Effects of eyeshades in sleep quality and pain after surgery in school-age children with supracondylar humeral fractures - Xiang-xuan Wang; Xiang-xuan Wang; Kai-nan Lin; Kai-nan Lin; Wen-chen Xu; Wen-chen Xu; Hui Chen; Hui Chen; Hao-qi Cai; Hao-qi Cai; Hao-qi Cai (Frontiers Media S.A., 2023)
ObjectiveThis study aimed to explore the effects of eye masks on the sleep quality and pain of children over 5 years old with humeral supracondylar fracture after surgery.MethodsFifty children with humeral supracondylar fracture who underwent closed reduction and percutaneous pinning (CRPP) in the Pediatric orthopaedic Department of a provincial hospital in China from February 2020 to December 2021 were selected. The children were randomly divided into the experimental group (n = 25) and the control group (n = 25). Children in the control group were given routine sleep care, and the children in the experimental group were given a sleep intervention with eye masks for three nights after surgery. The Pittsburgh Sleep Quality Index was used to evaluate the sleep quality of the children. The Children's Pain Behaviour Scale was used to evaluate the pain of the children.ResultsAfter three nights of receiving the eye mask intervention, the children in the experimental group had significantly lower sleep quality scores than those in the control group; the difference was statistically significant (p < 0.05), and the children in the experimental group had higher sleep quality. The experimental group's pain scores were significantly lower than the control group's, and the difference was statistically significant (p < 0.05), and the children in the experimental group experienced less post-operative pain.ConclusionsEye masks are a simple, safe and economical intervention, that is beneficial for improving the sleep quality and reducing pain in children over 5 years old with humeral supracondylar fracture after closed reduction and percutaneous pinning. It can be used as a reference and basis for clinical pain relief and sleep quality after surgery for supracondylar fractures of the humerus in children.